Therapists' experiences with internal representations of clients. Issue 3 (3rd July 2018) - Knox, Sarah; Cook, Jennifer; Knowlton, Graham; Hill, Clara E.
Abstract : Fourteen therapists were interviewed via telephone regarding their experience of "carrying around" their clients with them between sessions (i.e. internal representations, or IRs, of clients), a phenomenon about which little empirically based knowledge exists. Data were analyzed using consensual qualitative research. Findings indicated that overall, therapists have IRs infrequently, most often have IRs of clients struggling with severe or challenging presenting problems, and do receive some training about IRs. When describing a specific IR experience, therapists typically noted a strong therapy relationship, and stated that the IRs typically had specific triggers. The IRs generally consisted of feelings about the client, and typically consisted of thoughts about the client or the felt presence of the client. The IRs generally yielded positive effects, typically both personally and professionally, and were typically discussed with supervisors/consultants. Implications for research, training, and practice are presented.